Gender Earnings Differential In The Malaysian Manufacturing Sector - Cheong, Jia Qi (2018)
This study estimated the size of the male-female earnings differential in the Malaysian manufacturing sector and further decomposed it into the part that is explained by differences in endowments and the part that remains unexplained. Further decomposition was done by education levels, ethnicity, marital status, occupation groups, manufacturing subsectors, firm size, firm ownership and trade union membership. The data used was drawn from the Second Productivity and Investment Climate Survey (PICS II), 2006, conducted collaboratively by the World Bank, the Malaysian Department of Statistics, and the Economic Planning Unit.